Self-Directed Learning Readiness (SDLR) among Foundation Students from High and Low Proficiency Levels to Learn English Language (Malaysian Journal of Learning and Instruction, 2018)
Purpose â€“ In the field of second language education, self-directed learning is really important as it can empower students to attain optimal success in language learning by engaging students to express their ideas confidently, think reflectively and make use of language learning strategies. The main aim of the present study is to investigate studentsâ€™ self-directed learning readiness (SDLR) in a foundation program in a public university in Malaysia so as to find out how they perceive this approach can improve their learning of the English language at tertiary level. More specifically, the researchers intend to find answers to these research questions: 1) Are foundation students ready to use self-directed learning strategies in English Language learning? (i.e. awareness, motivation and language learning strategies); 2) Is there a significant difference in the three attributes (i.e., awareness, motivation and language learning strategies) of self-directed learning among foundation students?; and 3) Is there a significant difference between English language proficiency (upper and lower) and the three attributes (i.e., awareness, motivation, language learning strategies) in using self-directed learning strategies?Methodology â€“ A set of survey questionnaires with a 6-point Likert scale were administered to 400 students attending an English proficiency course (i.e., Introduction to Academic English) in the first semester of the Foundation Studies for Agricultural Science program. The data of the questionnaire were analyzed using descriptive statistics, independent samples t-test and paired samples t-test.Findings â€“ Results revealed that the respondents have a rather high degree of readiness to apply self-directed learning strategies in learning English. Motivation has the highest mean scores (M=4.57), followed by language learning strategies (M=4.41) and awareness (M=4.34). Results also showed that there are no difference in terms of SDLR depending on English proficiency levels, namely lower level (MUET Bands 1,2,3) and upper level (MUET Bands 4,5) (p>.05).Significance â€“ The findings are beneficial for students to learn more about their readiness to apply the self-directed learning strategies. In particular, these findings also provide insights for lecturers, program administrators, curriculum developers, and policy makers to plan and implement suitable teaching methods, course outlines, and curricula for the development of the studentsâ€™ English language abilities.